EFEKTIVITAS PENAGIHAN PAJAK DENGAN SURAT TEGURAN DAN SURAT PAKSA TERHADAP KONTRIBUSI PENERIMAAN PAJAK PADA KANTOR PELAYANAN PAJAK PRATAMA MAKASSAR SELATAN - Haeruddin Haeruddin (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2016)
The aim thisstudywas to assess the effectivity and contribution to the income tax collection Warning Letter and Distress Warrantto income tax revenue at Kantor Pelayanan Pajak Pratama Makassar Selatan. This study used descriptive analysis method qualitative and quantitative descriptive, data source is the primary datasource and secunder, where the source of this resear chobtained through interviews with several employees ofthe agency, direct observation and documentation. The results of this study indicate that income tax collection with Warning Letter and Distress Warrant2013, 2014, dan 2015 of Kantor Pelayanan Pajak PratamaMakassar Selatan relatively ineffective and contribution to the income tax collection Warning Letter and Distress Warrant against the income tax revenuein 2013, 2014, 2015 of Kantor Pelayanan Pajak Pratama Makassar Selatan relatively less. Cause melting Warning Letter and Letter Forced does not reach 100%, among others, tax insurerdid not recognize thetax debt, tax Insurersare notable topay off the tax debt, the personapplying for ataxinstallment payment for the financial condition does notallowif paid at the same time, tax Insurers filed an objection to the amount of tax arrears, and the insurer tax has failed. Advice that can be given is that the KPP Pratama Makassar Selatan can improve the performance of the billing section, so that the amount of the disbursement of arrears of income tax will increase and the amount of income tax arrears will be reduced.